NCAM1 modulates the proliferation and migration of pulmonary arterial smooth muscle cells in pulmonary hypertension - Yunwei Chen; Ningxin Liu; Yunjing Yang; Lingzhi Yang; Yan Li; Zhuo Qiao; Yumin Zhang; Ailing Li; Rui Xiang; Li Wen; Wei Huang (Respiratory Research)
Abstract Background Pulmonary hypertension (PH) is a malignant vascular disease characterized by pulmonary arterial remodeling. Neural cell adhesion molecule 1 (NCAM1) is a cell surface glycoprotein that is involved in a variety of diseases, including cardiovascular disease. However, the role of NCAM1 in PH remains underexplored. Methods Pulmonary hypertension models were established using monocrotaline in rats and hypoxia in mice. NCAM1 protein levels in plasma from patients and rats were measured by ELISA. Expression of NCAM1 in rat lung tissues were evaluated using qRT-PCR, Western blotting, and immunofluorescence. The effects of NCAM1 on rat pulmonary artery smooth muscle cells were studied by stimulating these cells with PDGF-BB. Results Elevated levels of NCAM1 protein and mRNA were observed in both PH patients and monocrotaline-induced PH rats. NCAM1 knockdown ameliorated hypoxia-induced PH, highlighting its role in pulmonary artery remodeling. In PASMCs, NCAM1 expression was upregulated by PDGF-BB stimulation, enhancing cell proliferation and migration. This effect was attenuated by NCAM1 knockdown but partially restored by an ERK1/2 pathway activator (tert-butylhydroquinone, TBHQ), suggesting NCAM1’s involvement in PASMC dynamics through the ERK1/2 signaling pathway. Conclusion Our findings confirm the role of NCAM1 in pulmonary arterial hypertension and demonstrate its promotion of PASMC proliferation and migration through the ERK1/2 signaling pathway.